2021
DOI: 10.4269/ajtmh.20-1297
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Pathways and Delays in Initiation of Treatment among Newly Diagnosed Tuberculosis Patients in Ballabgarh, India

Abstract: A delay in diagnosis and initiation of treatment in patients with tuberculosis (TB) can affect the period of communicability and cost of treatment. We aimed to describe the diagnostic pathways and delays in initiation of treatment among drug-sensitive newly diagnosed TB patients in Ballabgarh, India. In May 2019, we interviewed 110 TB patients who were put on treatment in the past 2 months. It was a cross-sectional study where data collection was conducted by a physician. We used a structured questionnaire to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The delay could be due to (a) overlap of TB and COVID-19 symptoms and the stigma they may face if they reveal the symptoms and are found positive for COVID-19 26 ) , (b) the primary focus of identifying and testing all suspected COVID-19 by healthcare providers and deployment of most of the health system resources in the prevention and control of COVID-19, and (c) transport-related problems. Previous studies during the pre-COVID-19 era across India have also reported a significant proportion as well as the duration of delays in the diagnosis and treatment of TB 27 , 28 , 29 ) .…”
Section: Discussionmentioning
confidence: 94%
“…The delay could be due to (a) overlap of TB and COVID-19 symptoms and the stigma they may face if they reveal the symptoms and are found positive for COVID-19 26 ) , (b) the primary focus of identifying and testing all suspected COVID-19 by healthcare providers and deployment of most of the health system resources in the prevention and control of COVID-19, and (c) transport-related problems. Previous studies during the pre-COVID-19 era across India have also reported a significant proportion as well as the duration of delays in the diagnosis and treatment of TB 27 , 28 , 29 ) .…”
Section: Discussionmentioning
confidence: 94%
“…If TB diagnosis is delayed, it can amplify the spread of infection, exacerbate illness severity, elevate mortality rates, and might be a factor contributing to the limited reduction in TB incidence, despite the worldwide expansion of the directly observed treatment, short course (DOTS). 1 Identifying the reasons behind delays can contribute to achieving India's goal of eliminating tuberculosis by 2025. Hence, a primary area of emphasis within India's National Tuberculosis Elimination Programme (NTEP) is rapid diagnosis and timely treatment.…”
Section: Introductionmentioning
confidence: 99%
“…2 Having information about the diagnostic routes is crucial for devising strategies to minimize the delays in diagnosis or treatment. 1 India possesses a multifaceted and diverse healthcare delivery structure, encompassing public and various forms of private healthcare providers, including both formal and informal sectors. Private and informal healthcare providers frequently serve as the initial point of contact for addressing illnesses, including tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…After reviewing the extensive literature, the problem of patient delay exists in almost all countries with a TB high burden, but the problem seems to be worse in developing countries. 25,29,30 This finding is related to the TB knowledge of citizens and the diagnostic level of primary medical institutions, 31,32 which may make TB control more difficult to achieve in poor countries. In addition, TB notification and timely treatment are also are impacted by the COVID-19 pandemic.…”
mentioning
confidence: 99%